Code-switching used in basboi's song lyrics on adulting for dummies album - Muhamad Fajar Dwiyanto; Cicih Nuraeni; Delis Meta Tiana (CV. Kalimasada Group Profesional, 2023)
The songs are one of the numerous types of media that can use code-switching English and Indonesia has some number of songs of this genre. Unlike the lyrics made by Basboi, he mixed Indonesian and English in one song and not just one song but made it into an album. This study aims to the types of Code-Switching, the reason used in code-switching, and the most frequently use of code-switching in the lyrics of Basboi’s song. This study used descriptive qualitative method that is carried out by colleting as much descriptive data as possible which is then presented in the form of reports and description. The writer used Poplack’s theory to find four types of code-switching in Adulting for Dummies album. The results showed that The types of code-switching in Adulting for Dummies album are Intra-Sentential Code-Switching, Inter-Sentential Code-Switching, Tag-Switching, and Establish Continuity Code-switching. The study discovered 4 data of Tag-Switching (8,51%), 20 data of Inter-Sentential Code-Switching (42,55%), 23 data of Intra-Sentential Code-Switching (48,94%).